A method for preparing high specific surface area porous carbon by pre-oxidation-gas phase nitrogen doping

CN122916095APending Publication Date: 2026-10-16QINGDAO HEIMAO NEW MATERIAL RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611034696.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]为了解决现有技术存在的不足,本申请提供一种预氧化-气相氮掺杂制备高比表面积多孔碳的方法,用以解决现有技术中传统氮掺杂多孔碳制备工艺中存在的“高氮掺杂量-低比表面积”权衡矛盾以及工艺复杂、规模化适配性差等的技术问题

Benefits of technology

本申请的预氧化-气相氮掺杂制备高比表面积多孔碳的方法,通过“先预氧化、后气相氮掺杂”的两段协同工艺,通过预氧化引入的含氧官能团和微孔结构为后续氨气掺杂提供了充足的活性位点和吸附位点,使氮掺杂效率显著提升,在碳晶格中高效引入吡啶氮,石墨氮等氮物种;同时,预氧化的可控刻蚀与二段氨气的活化造孔功能相辅相成,可大幅度提升多孔碳比表面积以及孔体积,避免了传统方法中高温掺氮导致比表面积不足的问题。实验数据表明,本申请方法制得的多孔碳比表面积可达2067.82 m²/g,氮含量可达7.02wt%,突破了现有技术中“高氮-低比表”或“高比表-低氮”的两难瓶颈。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916095A_ABST
    Figure CN122916095A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of carbon material modification, in particular to a method for preparing high specific surface area porous carbon through pre-oxidation and gas-phase nitrogen doping, which comprises the following steps: step one, pre-oxidation: placing pre-carbonized porous carbon powder in a CVD tube furnace, pre-oxidizing and keeping warm for a period of time in an oxygen-containing atmosphere after being heated to a first keeping warm temperature at a first heating rate in an inert atmosphere; step two, gas-phase nitrogen doping: switching the pre-oxidized carbon material to an inert atmosphere, heating to a second keeping warm temperature at a second heating rate, then introducing nitrogen-containing gas for nitrogen doping and keeping warm treatment, and switching to the inert atmosphere again for natural cooling after the treatment is completed. The oxygen-containing functional groups and microporous structures introduced through pre-oxidation provide sufficient active sites and adsorption sites for subsequent ammonia doping, so that the nitrogen doping efficiency is significantly improved; meanwhile, the controllable etching of pre-oxidation and the pore-creating function of the second ammonia activation complement each other, so that the specific surface area and pore volume of the porous carbon can be greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of carbon material modification technology, and in particular to a method for preparing high specific surface area porous carbon by pre-oxidation-gas phase nitrogen doping. Background Technology

[0002] Porous carbon materials, with their ultra-high specific surface area, controllable hierarchical pore structure, excellent chemical stability, and intrinsic electronic conductivity, have become one of the core research directions in the field of nano-carbon-based functional materials. These materials have demonstrated enormous application potential in several strategic emerging industries, including adsorption separation, heterogeneous catalysis, and electrochemical energy storage and conversion. Especially in the field of silicon-carbon anodes for new energy lithium batteries, porous carbon, as a supporting matrix for silicon-based active materials, is considered a key supporting material for overcoming the volume expansion problem of silicon materials during charge-discharge cycles and realizing the commercialization of high-energy-density lithium batteries. Therefore, the performance upgrade and industrialization breakthroughs of porous carbon materials are directly related to the development of next-generation energy storage technologies, possessing both strong technological necessity and industrial urgency.

[0003] However, traditional porous carbon preparation processes have long faced the technical bottleneck of synergistically optimizing specific surface area control and pore structure integrity, severely limiting their performance ceiling in high-end applications. Specifically, current mainstream preparation routes generally suffer from the following three core pain points, failing to simultaneously meet the industrial demands for high performance, low cost, and large-scale production: First, its specific surface area is a limitation. Due to inherent limitations in the manufacturing process, the specific surface area of ​​traditional porous carbon generally does not exceed 1000 m². 2 / g, while high-value-added applications such as silicon-carbon anodes and high-end catalysis generally require a specific surface area of ​​up to 1500m². 2 / g or more. Low specific surface area cannot support the core requirements of high adsorption capacity and high ion storage sites, directly limiting the upper limit of the material's application scenarios.

[0004] Second, the preparation process lacks universality. Physical activation methods (such as high-temperature steam activation, CO2 activation, etc.) have poor controllability, are prone to pore structure collapse, and have long reaction cycles; chemical activation methods or template methods rely too much on highly corrosive reagents or high-precision templates, requiring an additional 2 to 3 independent steps, significantly increasing the process complexity; hydrothermal synthesis methods have poor batch stability, with single batch capacity only in the kilogram range, which is completely unsuitable for the industrial-scale production needs of tons or more.

[0005] Third, existing gas-phase doping technologies suffer from a significant trade-off between doping and structure. To further improve the interfacial properties of porous carbon, nitrogen doping has become a core modification pathway for regulating the electronic structure and chemical properties of carbon materials. However, existing doping technologies mainly face two types of problems: in-situ doping introduces a nitrogen source and simultaneously carbonizes it during precursor synthesis, resulting in good nitrogen doping uniformity and stable bonding states, but the process is complex, raw material costs are high, and scalability is poor; post-processing doping is simple and cost-controllable, but the precision of doping amount and uniformity control is low. To achieve high nitrogen doping levels, it is usually necessary to increase the heat treatment temperature or extend the holding time, but high-temperature treatment easily triggers thermal reconstruction of the carbon framework, micropore collapse, and pore sintering, leading to a significant decrease in the specific surface area and pore volume of porous carbon. These problems ultimately lead existing technologies into a dilemma of "high nitrogen doping amount - low specific surface area" or "high specific surface area - low nitrogen doping amount," with the modification benefits of nitrogen doping being largely offset by structural degradation effects. Summary of the Invention

[0006] To address the shortcomings of existing technologies, this application provides a method for preparing high specific surface area porous carbon through pre-oxidation-gas phase nitrogen doping, which solves the technical problems of the trade-off between "high nitrogen doping amount and low specific surface area" and the complexity and poor adaptability to large-scale production in traditional nitrogen-doped porous carbon preparation processes.

[0007] This application provides a method for preparing high specific surface area porous carbon through pre-oxidation-gas phase nitrogen doping, comprising: Step 1, Pre-oxidation: The pre-carbonized porous carbon powder is placed in a CVD tube furnace and heated to the first holding temperature at the first heating rate under an inert atmosphere. Then, it is pre-oxidized and held at the oxygen-containing atmosphere for a period of time. Step 2, gas-phase nitrogen doping: After the pre-oxidized carbon material is switched to an inert atmosphere and heated to the second holding temperature at the second heating rate, ammonia-containing gas is introduced for nitrogen doping and holding treatment. After the treatment is completed, the inert atmosphere is switched again and the material is naturally cooled to room temperature to obtain the desired high specific surface area nitrogen-doped porous carbon.

[0008] Preferably, the pre-carbonized porous carbon powder is any one of biomass carbon, phenolic resin carbon, or coal-based porous carbon.

[0009] Preferably, the pre-carbonized porous carbon powder needs to be pre-crushed and sieved before pre-oxidation: the blocky or coarse-particle pre-carbonized porous carbon is placed in a crushing device for grinding, and the resulting powder is sieved through a standard sieve with a mesh size of 300.

[0010] Preferably, the oxygen-containing atmosphere is a mixed atmosphere formed by oxygen and an inert gas, wherein the volume fraction of oxygen in the pre-oxidation and heat preservation treatment is 5%-25%.

[0011] Preferably, the ammonia-containing gas is a mixture of ammonia and an inert gas, wherein the volume fraction of ammonia in the nitrogen-doped insulation treatment is 5%-20%.

[0012] Preferably, in steps one and two, the inert atmosphere is a mixed atmosphere formed by one or more of nitrogen, helium, neon, argon, krypton, xenon, and radon.

[0013] Preferably, in step one, the first heat preservation temperature is 300-550℃, and the heat preservation time of the pre-oxidation heat preservation is 60-360min.

[0014] Preferably, in step two, the second heat preservation temperature is 700-1000℃, and the processing time of the nitrogen doping heat preservation treatment is 60-240 min.

[0015] Preferably, both the first heating rate and the second heating rate are 2-5℃ / min.

[0016] Preferably, the pre-carbonized porous carbon powder is spread evenly in the corundum boat, and the corundum boat is placed in the center of the CVD tubular furnace.

[0017] The beneficial effects of this application are as follows: This application presents a method for preparing high specific surface area porous carbon through pre-oxidation and gas-phase nitrogen doping. This method employs a two-stage synergistic process of "pre-oxidation followed by gas-phase nitrogen doping." The oxygen-containing functional groups and microporous structure introduced by pre-oxidation provide ample active and adsorption sites for subsequent ammonia doping, significantly improving nitrogen doping efficiency and efficiently introducing nitrogen species such as pyridine nitrogen and graphitic nitrogen into the carbon lattice. Simultaneously, the controllable etching of pre-oxidation and the activation and pore-forming function of the second-stage ammonia process complement each other, greatly increasing the specific surface area and pore volume of the porous carbon, avoiding the problem of insufficient specific surface area caused by high-temperature nitrogen doping in traditional methods. Experimental data show that the porous carbon prepared by this method can achieve a specific surface area of ​​2067.82 m² / g and a nitrogen content of 7.02 wt%, overcoming the dilemma of "high nitrogen-low specific surface area" or "high specific surface area-low nitrogen" in existing technologies. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0019] Figure 1A flowchart illustrating the operational steps of the method for preparing high specific surface area porous carbon by pre-oxidation-gas phase nitrogen doping provided in the embodiments of this application; Figure 2 The adsorption-desorption isotherm curves of the pre-carbonized porous carbon powder raw material of this application are shown. Figure 3 The BJH pore size distribution curve of the pre-carbonized porous carbon powder raw material of this application; Figure 4 The adsorption-desorption isotherm curve of the high specific surface area nitrogen-doped porous carbon prepared in Example 1 of this application; Figure 5 The BJH pore size distribution curve of the high specific surface area nitrogen-doped porous carbon prepared in Example 1 of this application; Figure 6 The full X-ray photoelectron spectroscopy spectrum of the high specific surface area nitrogen-doped porous carbon prepared in Example 1 of this application; Figure 7 The fine-fit spectrum of C1s fine-fit of the high specific surface area nitrogen-doped porous carbon prepared in Example 1 of this application; Figure 8 This is a fine-fit spectrum of the N1s fine fit of the high specific surface area nitrogen-doped porous carbon prepared in Example 1 of this application. Detailed Implementation

[0020] The technical solutions of this application will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0021] The following is combined Figures 1-8 This application describes a method for preparing high specific surface area porous carbon using pre-oxidation-gas phase nitrogen doping, as provided in the embodiments of this application.

[0022] Reference Figure 1 As shown, this application provides a method for preparing high specific surface area porous carbon through pre-oxidation-gas-phase nitrogen doping. The method employs a two-stage synergistic activation treatment technology of pre-oxidation and gas-phase nitrogen doping. The specific process flow is as follows: Step 1, Pre-oxidation: Pre-carbonized porous carbon powder is placed in a CVD tube furnace. The pre-carbonized porous carbon powder can be any one of biomass carbon, phenolic resin carbon, or coal-based porous carbon. Before pre-oxidation, the powder needs to be pre-crushed and sieved: the lumpy or coarse-grained pre-carbonized porous carbon is ground in a grinding device such as a ball mill or air jet mill, and the resulting powder is sieved through a standard sieve with a mesh size of 300 mesh, i.e., sieved to a particle size ≤48μm. A certain amount of the sieved powder is then spread evenly in a corundum boat, which is placed in the center of the CVD tube furnace for heating and oxidation.

[0023] Before heating in the CVD tube furnace, inert gas is introduced to replace the air in the furnace chamber. Then, under the protection of the inert atmosphere, the temperature is increased to the first holding temperature at a first heating rate. Once the temperature reaches the first holding temperature, the furnace is switched to an oxygen-containing atmosphere for pre-oxidation and holding for a period of time. Specifically, the first heating rate is 2-5℃ / min; the first holding temperature is 300-550℃; the oxygen-containing atmosphere is a mixed atmosphere formed by mixing oxygen and inert gas, with oxygen accounting for 5%-25% of the gas volume in the CVD tube furnace; the pre-oxidation holding time is 60-360 min; and the inert atmosphere is a mixed atmosphere formed by one or more of nitrogen, helium, neon, argon, krypton, xenon, and radon.

[0024] Step 2, gas-phase nitrogen doping: After the pre-oxidation holding time is completed, the oxygen-containing atmosphere is switched back to an inert atmosphere, and the temperature is increased to the second holding temperature at the second heating rate. Once the second holding temperature is reached, nitrogen-containing gas is immediately introduced for nitrogen doping holding treatment. The second heating rate is 2-5℃ / min; the second holding temperature is 700-1000℃; the nitrogen-containing gas is a mixture of NH3 and an inert gas, with NH3 accounting for 5%-20% of the volume; and the nitrogen doping holding time is 60-240 min.

[0025] After the nitrogen doping and heat preservation treatment is completed, the atmosphere is switched to an inert atmosphere again for natural cooling to room temperature to obtain the desired high specific surface area nitrogen-doped porous carbon. Inert gas must be continuously introduced throughout the cooling process to protect the carbon material from oxidation or loss of nitrogen species at high temperatures.

[0026] In this process, the first step of pre-oxidation introduces oxygen-containing functional groups, providing more reactive sites for subsequent doping, increasing the specific surface area, creating a microporous structure, and enhancing the adsorption capacity of carbon materials for NH3, thereby strengthening the second-stage doping capability and increasing the nitrogen content. After the first-stage pre-oxidation process, the oxygen-containing functional groups and oxygen defect sites react with NH3 at high temperature to generate intermediates such as amides and nitriles, which are then pyrolyzed into nitrogen-doped carbon and incorporated into the carbon lattice to become nitrogen species such as pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen, thus improving the doping efficiency. At the same time, the second-stage ammonia treatment can simultaneously activate and dope nitrogen.

[0027] In other words, this application fundamentally overcomes the trade-off between "high nitrogen doping amount and low specific surface area" in traditional technologies by employing a two-stage synergistic process of "pre-oxidation to create pores and enrich oxygen sites, followed by gas-phase nitrogen doping". The first stage, oxygen-containing gas pre-oxidation treatment, involves moderate etching of the pre-carbonized powder at a reasonable temperature. This not only significantly increases the specific surface area of ​​porous carbon and creates a microporous structure, but also introduces abundant oxygen-containing functional groups and oxygen defect sites onto the carbon framework surface. These oxygen-containing sites serve as reactive centers for subsequent doping, greatly enhancing the adsorption and capture capacity of carbon materials for ammonia molecules.

[0028] In particular, during the second stage of high-temperature gas-phase doping, the oxygen-containing functional groups introduced in the pre-treatment react with NH3 to generate intermediates such as amides and nitriles, which are then pyrolyzed and reconstructed into nitrogen-doped carbon (pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen, etc.), significantly improving the doping efficiency. At the same time, ammonia gas also has the effect of activating and creating pores at high temperatures, further expanding the pore volume. This process avoids the pore blockage problem caused by traditional solid-phase mixed dopants, achieving efficient nitrogen doping (≥5%) while synergistically increasing the specific surface area (≥1000 m² / g).

[0029] Furthermore, the entire preparation process of this application is completed continuously in a single CVD tube furnace, eliminating the need for highly corrosive chemical reagents or complex templates, greatly simplifying the process and making it suitable for ton-scale industrial production. By adjusting process parameters such as pre-oxidation temperature, oxygen concentration, nitrogen doping temperature, and NH3 concentration, the pore structure and nitrogen doping degree of porous carbon can be precisely controlled, resulting in a final product with hierarchical pore characteristics of 0-2 nm micropore enrichment and 2-5 nm mesopore distribution, exhibiting significant performance potential.

[0030] Reference Figure 2-8 As shown, to make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with specific embodiments: Example 1 The pre-carbonized porous carbon powder was ground in a ball mill for 30 minutes. In this embodiment, phenolic resin-based pre-carbonized carbon powder was selected. The ground powder was sieved through a 300-mesh standard sieve, and the sieved material was used for later use.

[0031] Weigh approximately 10g of the pre-carbonized porous carbon powder after sieving, and spread it evenly in a semi-circular corundum boat. Place the corundum boat in the center of the CVD tube furnace. Before heating, introduce high-purity nitrogen gas with a purity ≥99.999% into the furnace at a flow rate of 200 mL / min to replace the air inside the furnace and ensure that the system is under inert atmosphere protection.

[0032] The furnace temperature was then raised to 400℃ at a heating rate of 3℃ / min. Once the set temperature was reached, the atmosphere was switched to a 15% O2 / N2 mixture, creating a mixed atmosphere with an oxygen volume fraction of 15% and a nitrogen volume fraction of 85% inside the CVD tube furnace. The furnace was then pre-oxidized and held at this atmosphere for 180 min.

[0033] After the pre-oxidation and heat preservation are completed, the atmosphere is switched back to high-purity nitrogen, and the furnace temperature is raised to 850℃ at a heating rate of 4℃ / min. After reaching the set temperature, the atmosphere is immediately switched to a 15% NH3 / Ar mixture, so that the volume fraction of NH3 in the furnace gas is 15% and the integral number of argon gas is 85%. Nitrogen doping heat preservation treatment is carried out under this atmosphere for 180 min.

[0034] After the nitrogen doping and heat preservation treatment is completed, the atmosphere is switched to high-purity nitrogen again, and the furnace body is allowed to cool down naturally to room temperature under nitrogen protection. The corundum boat is then removed, and high specific surface area nitrogen-doped porous carbon is obtained.

[0035] Example 2 The only difference between this embodiment and Embodiment 1 is that the pre-oxidation and heat preservation temperature in step one is set to 325℃, while the other steps and parameters are the same as in Embodiment 1.

[0036] Example 3 The only difference between this embodiment and Embodiment 1 is that the pre-oxidation and heat preservation temperature in step one is set to 550℃, while the remaining steps and parameters are consistent with those in Embodiment 1.

[0037] Example 4 The only difference between this embodiment and Embodiment 1 is that the nitrogen doping holding temperature in step two is set to 700℃ and the holding time is set to 120 min. All other steps and parameters are the same as in Embodiment 1.

[0038] Example 5 The only difference between this embodiment and Embodiment 1 is that the nitrogen doping holding temperature in step two is set to 1000℃ and the holding time is set to 120 min. All other steps and parameters are the same as in Embodiment 1.

[0039] Comparative Example 1 This comparative example only undergoes pre-oxidation treatment and does not involve two-stage nitrogen doping. The specific steps are as follows: Following the method in Example 1, the pre-carbonized porous carbon powder was sieved and spread out, then placed in a CVD tube furnace. Under nitrogen protection, the temperature was increased to 400°C at a rate of 3°C / min. The furnace was then switched to a 15% O2 / N2 mixed gas and held at this temperature for 180 min. Subsequently, the furnace was switched back to nitrogen and allowed to cool naturally to room temperature under nitrogen protection. Thus, the resulting sample underwent only pre-oxidation treatment and was not nitrogen-doped.

[0040] Comparative Example 2 The only difference between this comparative example and Comparative Example 1 is that the pre-oxidation holding temperature is set to 320℃, while the other steps and parameters are the same as those in Comparative Example 1.

[0041] Comparative Example 3 The only difference between this comparative example and Comparative Example 1 is that the pre-oxidation holding temperature is set to 550℃, while the other steps and parameters are the same as those in Comparative Example 1.

[0042] Comparative Example 4 This comparative example does not undergo pre-oxidation treatment; it directly performs a two-stage nitrogen doping treatment. The specific steps are as follows: Following the method in Example 1, the pre-carbonized porous carbon powder was sieved and spread out, then placed in a CVD tube furnace. Under nitrogen protection, the temperature was directly raised to 850°C at a heating rate of 3°C / min. Once the set temperature was reached, the temperature was immediately switched to a 15% NH3 / Ar mixed gas and held for 180 min. Subsequently, the temperature was switched back to nitrogen and allowed to cool naturally to room temperature under nitrogen protection. The resulting sample had not undergone pre-oxidation treatment, but only NH3 nitrogen doping treatment.

[0043] Performance testing and results analysis: The samples prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to specific surface area and pore structure analysis (BET method) and elemental composition analysis (EA method), respectively. The test results are shown in Table 1 and Table 2.

[0044] Table 1. Specific surface area and pore structure parameters of samples from each embodiment and comparative example.

[0045] Table 2. Elemental composition (EA analysis) of each example and comparative sample.

[0046] As can be seen from the data in Table 1: First, comparing Example 1 with Comparative Examples 1-3, it can be seen that the specific surface area of ​​Comparative Examples 1-3, which underwent only single pre-oxidation treatment, is 416-508 m². 2 / g, compared with raw materials (410.45 m) 2 The surface area of ​​the micropores is increased compared to that of g; and after the pre-oxidation in step one and the two-stage NH3 synergistic treatment in step two, the specific surface area is significantly increased to 1473-2068 m², as in Examples 1-3. 2 / g. This indicates that although pre-oxidation itself cannot significantly increase the specific surface area, the oxygen-containing functional groups and micropores it introduces provide the necessary conditions for subsequent NH3 activation, and there is a significant synergistic effect between pre-oxidation and NH3 doping.

[0047] Secondly, comparing Examples 1-3, it is evident that the pre-oxidation temperature has a significant impact on the specific surface area of ​​the final product. The highest specific surface area, 2067.82 m², was achieved at the pre-oxidation temperature of 400°C (as in Example 1). 2 / g; When the temperature is too low, such as 325°C in Example 2, the degree of oxidation is insufficient, the synergistic activation effect is limited, and the specific surface area is low, only 1472.72 m². 2 / g; When the temperature is too high, such as 550℃ in Example 3, the carbon material is prone to over-ablation, which reduces the space for subsequent NH3 activation and pore formation, resulting in a decrease in specific surface area to 1739.66 m². 2 / g, but still significantly higher than the comparative example. This demonstrates that a suitable pre-oxidation temperature is also crucial for the synergistic effect; in this embodiment, after experimental comparison, 400℃ is preferred.

[0048] Third, comparing Examples 1, 4, and 5, it can be seen that the NH3 doping temperature also has a significant impact on the specific surface area of ​​the product. When the NH3 doping temperature is 850℃ (Example 1), the specific surface area and total pore volume of the product both reach their highest values ​​(2067.82 m²). 2 / g, 1.18 cm³ / g); when the temperature is too low (700℃, Example 4), the NH3 activation reaction activity is insufficient, and the specific surface area is only 780.27 m². 2 / g; When the temperature is too high (1000℃, Example 5), the carbon skeleton ablation intensifies, and the specific surface area and pore volume decrease compared to Example 1, but still remain at a high level (2037.68 m). 2 Therefore, the NH3 doping temperature needs to be controlled within a suitable range to achieve a balance between pore-forming effect and framework retention.

[0049] Fourth, comparing Example 1 and Comparative Example 4, it can be seen that although Comparative Example 4 also used NH3 treatment conditions of 850℃ / 180 min, it did not undergo pre-oxidation treatment, and its specific surface area was only 1353.41 m².2 / g, far lower than Example 1 (2067.82 m 2 / g). This fully demonstrates the key role of pre-oxidation treatment in improving the pore-forming efficiency of NH3 activation, and it can be determined that the oxygen-containing functional groups and micropores introduced by pre-oxidation can significantly enhance the adsorption and reactivity of carbon materials for NH3.

[0050] As can be seen from the data in Table 2: The nitrogen content in Examples 1-3 ranged from 5.02 to 7.02 wt%, all higher than 5 wt%, significantly better than Comparative Examples 1-3 (nitrogen-free), proving that the method of this application can indeed efficiently achieve nitrogen doping. The nitrogen content in Comparative Example 4 was 7.12 wt%, slightly higher than that in Example 1, but its specific surface area was much lower than that in Example 1. This shows that targeting only high nitrogen content will reduce the specific surface area, resulting in limited practical application value.

[0051] Comparing Examples 1-5, it is evident that temperature is a key parameter for controlling nitrogen content during nitrogen doping. When the NH3 doping temperature is 700℃ (Example 4), the nitrogen content is only 0.98 wt%, indicating insufficient reactivity of NH3 with carbon materials at this temperature. When the temperature is increased to 850℃ (Example 1), the nitrogen content increases significantly to 7.02 wt%. However, when the temperature is further increased to 1000℃ (Example 5), the nitrogen content decreases to 3.12 wt%, indicating that excessively high temperatures not only exacerbate carbon framework ablation but also cause the already incorporated nitrogen species to be lost due to insufficient thermal stability. Therefore, a suitable doping temperature range is crucial for achieving high nitrogen content, and in this example, after experimental comparison, 850℃ is preferred.

[0052] Furthermore, it can be seen that the promoting effect of pre-oxidation treatment in the nitrogen doping process is reflected in the function of oxygen-containing functional groups. Comparative Example 4, without pre-oxidation treatment, although also achieving a high nitrogen content (7.12 wt%), had extremely low residual oxygen content in its carbon material (0.67 wt%). This indicates that the strong reducing power of NH3 significantly removed a large amount of the original small amount of oxygen-containing groups on the carbon material surface, resulting in nitrogen doping mainly relying on the direct reaction between NH3 and the carbon skeleton. This single reaction pathway is not conducive to the formation of diverse nitrogen species. In contrast, Example 1, after pre-oxidation treatment, had an oxygen content of 4.11 wt%, significantly higher than Comparative Example 4. This indicates that the oxygen-containing functional groups introduced by pre-oxidation not only provide more active sites for nitrogen doping but also alleviate the problem of excessive removal of oxygen species caused by the strong reducing power of NH3 to some extent, which is beneficial to the formation of various active nitrogen species such as pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen.

[0053] Furthermore, such as Figure 4 and Figure 5As shown, the pore structure of the high specific surface area nitrogen-doped porous carbon prepared in Example 1 was analyzed. Its N2 adsorption-desorption isotherm exhibits typical Type IV isotherm characteristics, with a significant hysteresis loop appearing in the medium-to-high relative pressure region (P / P0 = 0.4-0.9), indicating that the material is rich in mesoporous structures. Its BJH pore size distribution curve shows that the pore size is mainly concentrated in the 2-5 nm range, further confirming the existence of mesoporous structures. These mesoporous characteristics facilitate the rapid diffusion and transport of electrolyte ions or reactant molecules within the porous carbon, giving the material significant advantages in electrochemical energy storage fields such as supercapacitors and silicon-carbon anodes for lithium-ion batteries.

[0054] In addition, such as Figure 6-8 As shown, XPS fine spectroscopy analysis revealed that nitrogen in the nitrogen-doped porous carbon prepared in Example 1 exists primarily in four forms: pyridine nitrogen (N-6, binding energy approximately 398.6 eV), pyrrole nitrogen (N-5, binding energy approximately 400.2 eV), graphitic nitrogen (NQ, binding energy approximately 401.3 eV), and nitrogen oxides (N-0, binding energy approximately 402.5 eV). Pyridine nitrogen and pyrrole nitrogen are considered beneficial for improving the pseudocapacitive properties of carbon materials, while graphitic nitrogen is beneficial for improving the electronic conductivity. The coexistence of these multiple nitrogen species enables the material to exhibit excellent performance in various application scenarios.

[0055] In summary, the pre-oxidation-gas-phase nitrogen doping method for preparing high specific surface area porous carbon provided in this application effectively solves the technical challenge of achieving both high specific surface area and high nitrogen content in traditional methods through the synergistic effect of pre-oxidation and gas-phase nitrogen doping. The oxygen-containing functional groups and structural defects introduced through the pre-oxidation process provide reactive sites for subsequent NH3 doping and create preconditions for NH3 activation and pore formation through gentle oxidation etching. The second stage, involving gas-phase nitrogen doping with NH3, simultaneously achieves efficient nitrogen doping and activation / pore formation, further enhancing the specific surface area and pore volume. Furthermore, both stages are completed continuously in a CVD tube furnace, resulting in a simple and efficient process with promising prospects for industrial application.

[0056] In the description of this application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc., indicating the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application.

[0057] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0058] In this application, unless otherwise expressly specified and limited, the terms "installation," "connection," "linking," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection, an electrical connection, or a connection that allows communication between components; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components, unless otherwise expressly limited. Those skilled in the art can understand the specific meaning of the above terms in this application based on the specific circumstances.

[0059] In this application, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0060] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.

Claims

1. A method for preparing high specific surface area porous carbon through pre-oxidation-gas-phase nitrogen doping, characterized in that, include: Step 1, Pre-oxidation: The pre-carbonized porous carbon powder is placed in a CVD tube furnace and heated to the first holding temperature at the first heating rate under an inert atmosphere. Then, it is pre-oxidized and held at the oxygen-containing atmosphere for a period of time. Step 2, gas-phase nitrogen doping: After the pre-oxidized carbon material is switched to an inert atmosphere and heated to the second holding temperature at the second heating rate, ammonia-containing gas is introduced for nitrogen doping and holding treatment. After the treatment is completed, the inert atmosphere is switched again and the material is naturally cooled to room temperature to obtain the desired high specific surface area nitrogen-doped porous carbon.

2. The method for preparing high specific surface area porous carbon by pre-oxidation-gas phase nitrogen doping according to claim 1, characterized in that, The pre-carbonized porous carbon powder is any one of biomass carbon, phenolic resin carbon, or coal-based porous carbon.

3. The method for preparing high specific surface area porous carbon by pre-oxidation-gas-phase nitrogen doping according to claim 2, characterized in that, Before pre-oxidation, the pre-carbonized porous carbon powder needs to be crushed and sieved: the blocky or coarse-particle pre-carbonized porous carbon is placed in a crushing device for grinding, and the resulting powder is sieved through a standard sieve with a mesh size of 300.

4. The method for preparing high specific surface area porous carbon by pre-oxidation-gas phase nitrogen doping according to claim 1, characterized in that, The oxygen-containing atmosphere is a mixed atmosphere formed by oxygen and inert gas, wherein the volume fraction of oxygen in the pre-oxidation and heat preservation treatment is 5%-25%.

5. The method for preparing high specific surface area porous carbon by pre-oxidation-gas phase nitrogen doping according to claim 1, characterized in that, The ammonia-containing gas is a mixture of ammonia and an inert gas, wherein the volume fraction of ammonia in the nitrogen-doped insulation treatment is 5%-20%.

6. The method for preparing high specific surface area porous carbon by pre-oxidation-gas phase nitrogen doping according to claim 1, characterized in that, In steps one and two, the inert atmosphere is a mixed atmosphere formed by one or more of nitrogen, helium, neon, argon, krypton, xenon, and radon.

7. The method for preparing high specific surface area porous carbon by pre-oxidation-gas phase nitrogen doping according to claim 1, characterized in that, In step one, the first heat preservation temperature is 300-550℃, and the heat preservation time of the pre-oxidation heat preservation is 60-360min.

8. The method for preparing high specific surface area porous carbon by pre-oxidation-gas phase nitrogen doping according to claim 1, characterized in that, In step two, the second heat preservation temperature is 700-1000℃, and the processing time of the nitrogen doping heat preservation treatment is 60-240min.

9. The method for preparing high specific surface area porous carbon by pre-oxidation-gas phase nitrogen doping according to claim 1, characterized in that, The first heating rate and the second heating rate are both 2-5℃ / min.

10. The method for preparing high specific surface area porous carbon by pre-oxidation-gas phase nitrogen doping according to claim 1, characterized in that, The pre-carbonized porous carbon powder is spread evenly in the corundum boat, and the corundum boat is placed in the center of the CVD tubular furnace.